Workplace Wellness Program Employees' Perceptions and Expectations toward an Internal Employee Assistance Services - Sapora Sipon; Nurhafizah Yaacob (Institute of Research Engineers and Doctors, 2024)
Personal problems inside and outside of the workplace might effect on the employee performance. Employee Assistance Services (EAS) not only provide confidential, short-term counseling and longer-term referrals for employees and their family members but also prevention courses as well as online assistance services. This paper reports the analysis of the educational service employees' perceptions toward help-seeking through counseling services and their expectations toward the development of an internal Employee Assistance Services at their workplace. Data collection included reviews of internal reports, employee surveys and focus group discussions with the administrative stakeholders. A total of 583 questionnaires were collected from the employees in the educational institutes in Gombak District, Selangor State. The findings indicated that employees' perceptions toward help-seeking through counseling services were at the moderate level and their expectations toward Employee Assistance Services as a workplace wellness program were rated highly agreed. The administrative stakeholders also agreed and showed high level of endorsement toward the program. They hope to meet or exceed the original start-up goals and that employees will be satisfied with the services. Administrative stakeholders also perceived the EAS as "having a good return-on-investment value", and the Employee Assistance Services development will be compared favorably to a benchmark organization.